Peningkatan Hasil Belajar Guling Depan melalui Direct Instruction Visual di Kelas VII: Systematic Literature Review - Padilah, Nur; Mashud (SPRINTER: Jurnal Ilmu Olahraga, 2025)
This study aims to examine the effectiveness of the direct instruction learning model combined with visual media in improving the learning outcomes of specific forward rolls in seventh-grade junior high school students. Through a Systematic Literature Review (SLR) approach, the author identified, evaluated, and synthesized relevant research results published in the last five years (2020–2024) using Google Scholar and Crossref databases. The search strategy was based on the PICO method and literature selection using the PRISMA flow. A total of seven articles were analyzed qualitatively. Based on the results of the study, it was found that the application of direct instruction had a real impact on improving basic motor skills, especially when combined with the use of visual media such as demonstrative video displays, movement animations, and gradually arranged image illustrations. These findings reinforce the importance of explicit and multimodal learning strategies in physical education.